Apparent diffusion coefficient by magnetic resonance cholangiopancreatography is useful for grading cholecystitis and surgery planning. Issue 2 (30th September 2022) - Kurata, Yoshihiro; Hayano, Koichi; Imai, Yasuo; Ichinose, Masanori; Hirata, Atsushi; Mizumachi, Ryoya; Hirasawa, Soichiro; Yonemoto, Shohei; Sasaki, Takuma; Kainuma, Shunsuke; Takahashi, Yumiko; Ohira, Gaku; et al.
Abstract: Introduction: Laparoscopic cholecystectomy is a standard procedure for treating cholescytitis, but severe inflammation may cause complications. Our previous study showed that the apparent diffusion coefficient (ADC) values could predict difficult surgery. In the present study, relevance of ADC values in grading the severity of cholecystitis was pathologically investigated. Methods: We retrospectively analyzed a total of 50 patients who underwent laparoscopic cholecystectomy or laparotomic cholecystectomy/choledocholithotomy. The degree of inflammation in the neck of the gall bladder was pathologically graded into three tiers (grade 1, mild; grade 2, moderate; grade 3, severe), and ulceration, lymphoid follicle formation, and wall thickness of the gallbladder neck were recorded. All factors were statistically compared with the measured ADC values. Results: The ADC value was significantly lower in the severe inflammation group ( grade 3) than in the weak inflammation group (grades 1 and 2) (1.93 ± 0.22 vs 2.38 ± 0.67, respectively; P  = .02). Ulceration and wall thickness in the gallbladder neck were significantly correlated with ADC values ( P  = .04 and .006, respectively), and lymphoid follicle formation was marginally correlated with ADC values ( P  = .06). The diagnostic utility of the ADC values decreased as the interval between imaging and cholecystectomy increased. [Correction added on 19 October 2022, after first online publication: [On the first sentence of the Results section, (grades 2 and 3) for weak inflammation group has been changed to (grades 1 and 2).] Conclusion: ADC values were inversely associated with the pathologic intensity of cholecystitis. We recommend that the ADC value be measured before surgery, so that the procedure can be accordingly planned.